Hipertrofia da visão inflação do imaginário: um estudo empírico sobre a produção e recepção de sentidos pelo corpo da mulher cega numa sociedade escopofílica - Moraes, Marcelo Santos de (2008)
This work takes as a beginning point the conception that image, now days, can be consedered the most important social code. This hipotesis is formulated through a systemic approach, inside the communicational field, attempting to the movements of meaning production, reception and mediation. On one side, there is a technovision making human eyes perceiving up to 80% of everything men receives from outside, and in the other, the increasing conditioning of cognition and psych to visual information; between both, the image itself unavoidably corporeal -, assuming the position of mediator of social representations. As a counterpoint, it have been decided to study blind women, trying to understand how they deal with an environment that claims, especially from females, the corporal adoration - the feminine identity itself -, propagated by publicity, movies, television, it means, the vidoesphere proposed by Debray. Among the results, it was possible to evidence that even without seeing, many blind women cares about the visual universe, trying, somehow, to insert themselves on it for social interaction